A clinical model to identify patients with high-risk coronary artery disease - Yang, Yelin; Chen, Li; Yam, Yeung; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor Y.; Chinnaiyan, Kavitha; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2015)
This study sought to develop a clinical model that identifies patients with and without high-risk coronary artery disease (CAD).Although current clinical models help to estimate a patient's pre-test probability of obstructive CAD, they do not accurately identify those patients with and without high-risk coronary anatomy.Retrospective analysis of a prospectively collected multinational coronary computed tomographic angiography (CTA) cohort was conducted. High-risk anatomy was defined as left main diameter stenosis >=50%, 3-vessel disease with diameter stenosis >=70%, or 2-vessel disease involving the proximal left anterior descending artery. Using a cohort of 27,125, patients with a history of CAD, cardiac transplantation, and congenital heart disease were excluded. The model was derived from 24,251 consecutive patients in the derivation cohort and an additional 7,333 nonoverlapping patients in the validation cohort.The risk score consisted of 9 variables: age, sex, diabetes, hypertension, current smoking, hyperlipidemia, family history of CAD, history of peripheral vascular disease, and chest pain symptoms. Patients were divided into 3 risk categories: low (<=7 points), intermediate (8 to 17 points) and high (>=18 points). The model was statistically robust with area under the curve of 0.76 (95% confidence interval [CI]: 0.75 to 0.78) in the derivation cohort and 0.71 (95% CI: 0.69 to 0.74) in the validation cohort. Patients who scored <=7 points had a low negative likelihood ratio (<0.1), whereas patients who scored >=18 points had a high specificity of 99.3% and a positive likelihood ratio (8.48). In the validation group, the prevalence of high-risk CAD was 1% in patients with <=7 points and 16.7% in those with >=18 points.We propose a scoring system, based on clinical variables, that can be used to identify patients at high and low pre-test probability of having high-risk CAD. Identification of these populations may detect those who may benefit from a trial of medical therapy and those who may benefit most from an invasive strategy.
EVALuna2:12062